Investigation of spectral characteristics of cholesteric liquid crystals at carbohydrates influence - Vistak, Mariya; Dmytrakh, Vasyl; Horbenko, Yulia; Sushynskyi, Orest (Eastern-European Journal of Enterprise Technologies, 2016)
The concept of cholesteric liquid crystal interaction with carbohydrates to create the active medium of the primary sensor converter is considered. It is proposed to use the cholesteric liquid crystal with the reflection band in the visible spectrum as the sensing element of optical carbohydrate sensors. The information signal in such sensors is formed by selective reflection (transmission) of light in the sensitive medium of primary converters of optical sensors. The analysis of the data shows that the reason for the areas of abnormal behavior of the pitch at high concentrations of the aqueous carbohydrate solution is the interface. It is shown that there is a general tendency to reduce the pitch of the supramolecular helical structure with increasing concentration of aqueous solutions in all investigated carbohydrates. Furthermore, the maximum sensitivity of the cholesteric matrix is observed at low concentrations of the solution used for their detection. The highest spectral sensitivity is observed in aqueous fructose solutions.